The Italian occupation of Albania 1939 and the international reactions to it Dr. Youssef Taha Hussein - Hussein, Ass.Prof Dr. Youssef Taha (Thi Qar Arts Journal, 2023)
This study aims to give a picture of the nature of the policy pursued by Italy towards Albania since the end of the First World War until its occupation of Albania on April 7, 1939 and the international reactions that resulted from this occupation, at the forefront of which is the position of the United States of America and Britain, relying on a number of sources, foremost of which are the documents of the US Department of State that shed light on the important facts necessary that accompanied those positions under study. Published under the title: Foreign Relations of the United States Diplomatic Papers, 1939, General, The British Commonwealth and Europe, Absorption of Albania by Italy ,Volume II, Washington,1956. Referred to in short (F.R.U.S). Albania is one of the Balkan countries located in southeastern Europe, bordered by Montenegro to the northwest, Kosovo to the northeast, the Republic of Macedonia to the east, and Greece to the south and southeast, and Albania overlooks the Adriatic Sea to the west, while it overlooks the Ionian Sea to the southwest, and its total area is about 28,748 km2, while the population reaches 3,020,209 people, according to the latest available statistic for the year 2014 .